r = 0,5 Ом
Объяснение:
Дано:
R₁ = 2,5 Ом
I₁ = 0,5 А
R₂ = 1 Ом
I₂ = 1 А
r - ?
Закон Ома для полной цепи:
I = ЭДС / (R+r)
или
ЭДС = I*(R+r)
Дважды запишем:
ЭДС = I₁*(R₁+r) (1)
ЭДС = I₂*(R₂+r) (2)
Из (1) вычтем (2)
0 = I₁*(R₁+r) - I₂*(R₂+r)
0,5*(2,5+r) - 1*(1 + r) = 0
1,25 + 0,5*r - 1 -r = 0
1,25 - 1 = r - 0,5*r
0,25 = 0,5*r
r = 0,25/0,5 = 0,5 Ом
0,5 Ом
Закон ома для полной цепи
E=I1*(R1+r)
E=I2*(R2+r)
I1*(R1+r) = I2*(R2+r)
I1*R1 - I2*R2=(I2-I1)*r
r=(I1*R1 - I2*R2) / (I2-I1)=(2.5*0.5 - 1*1) / (1-0.5)= 0.5 Ом
r = 0,5 Ом
Объяснение:
Дано:
R₁ = 2,5 Ом
I₁ = 0,5 А
R₂ = 1 Ом
I₂ = 1 А
r - ?
Закон Ома для полной цепи:
I = ЭДС / (R+r)
или
ЭДС = I*(R+r)
Дважды запишем:
ЭДС = I₁*(R₁+r) (1)
ЭДС = I₂*(R₂+r) (2)
Из (1) вычтем (2)
0 = I₁*(R₁+r) - I₂*(R₂+r)
или
0,5*(2,5+r) - 1*(1 + r) = 0
1,25 + 0,5*r - 1 -r = 0
1,25 - 1 = r - 0,5*r
0,25 = 0,5*r
r = 0,25/0,5 = 0,5 Ом
0,5 Ом
Объяснение:
Закон ома для полной цепи
E=I1*(R1+r)
E=I2*(R2+r)
I1*(R1+r) = I2*(R2+r)
I1*R1 - I2*R2=(I2-I1)*r
r=(I1*R1 - I2*R2) / (I2-I1)=(2.5*0.5 - 1*1) / (1-0.5)= 0.5 Ом